Association of area‐level socioeconomic status and non–small cell lung cancer stage by race/ethnicity and health care–level factors: Analysis of the National Cancer Database. Issue 16 (20th June 2022) - Gupta, Anjali; Omeogu, Chioma H.; Islam, Jessica Y.; Joshi, Ashwini R.; Akinyemiju, Tomi F.
Abstract : Background: This study examined whether the association of socioeconomic status (SES) and non–small cell lung cancer (NSCLC) stage varied by race/ethnicity and health care access measures. Methods: This study used data from the 2004–2016 National Cancer Database for patients aged 18–89 years who had been diagnosed with Stage 0–IV NSCLC. Adjusted odds ratios (aORs) with 95% confidence intervals (CIs) were calculated for the associations of area‐level SES with an advanced stage at diagnosis via multilevel, multivariable logistic regression. The stage at diagnosis was dichotomized into early (0–II) and advanced (III–IV) stages, and area‐level SES was categorized on the basis of the patient's zip code level: (1) the proportion of adults aged ≥25 years without a high school degree and (2) the median household income. The models were stratified by race/ethnicity (non‐Hispanic [NH] White, NH Black, Hispanic, Asian, American Indian/Alaskan Native, and Native Hawaiian/Pacific Islander), insurance status (none, government, and private), and health care facility type (community, comprehensive community, academic/research, and integrated network). Results: The study population included 1, 329, 972 patients. Although only 17% of the NH White patients were in the lowest income quartile, 50% of the NH Black patients were in this group. Lower area‐level education and income were associated with higher odds of an advanced‐stage diagnosis (aOR for education, 1.12; 95% CI, 1.10–1.13; aOR for income, 1.13; 95% CI, 1.11–1.14). These associations persisted among NH White, NH Black, Hispanic, and Asian patients; among those with government and private insurance (but not the uninsured); and among those treated at each facility type. Conclusions: Area‐level income and education are strongly associated with an advanced NSCLC diagnosis regardless of the facility type and among those with government and private insurance. Abstract : Area‐level socioeconomic factors, specifically income and education, are strongly associated with an advanced non–small cell lung cancer diagnosis. These associations persisted among non‐Hispanic White, non‐Hispanic Black, Hispanic, and Asian patients; among those with government and private insurance; and among those treated at each facility type (community, comprehensive community, academic/research, and integrated network).